The PENGARUH KUALITAS PELAYANAN DESA GERENDONG TERHADAP KEPUASAN MASYARAKAT: PENGARUH KUALITAS PELAYANAN DESA GERENDONG TERHADAP KEPUASAN MASYARAKAT - Hayati Hayati; Ahmadi (NIAGARA Scientific Journal, 2023)
ABSTRACT The village is one of the government institutions that provide frontline services to the community in the village area concerned. Therefore, the existence of villages is the spearhead of the development of the nation's progress. Along with the importance of maximum service in a village, it is expected that the village government apparatus has the capacity and capability in accordance with the main tasks and functions of serving the community. Therefore, the village has an important role in paying attention to service quality. The aims study of were to analyze the effect of Gerendong Village service quality on community satisfaction. Purposive samping methode is applied to obtain 95 respondents, then analyzed by descriptive analysis and SEM-PLS. The result showed that service quality of Gerendong Village have positive effect and significant on community satisfaction. Key Words: Community Satisfaction, Service Quality, Satisfaction